When Societal Norms and Social Identity Collide: The Race Talk Dilemma for Racial Minority Children. (November 2015) - Pauker, Kristin; Apfelbaum, Evan P.; Spitzer, Brian
Racial minorities face a unique "race talk" dilemma in contemporary American society: Their racial background is often integral to their identity and how others perceive them, yet talk of race is taboo. This dilemma highlights the conflict between two fundamental social processes: social identity development and social norm adherence. To examine how, and with what costs, this dilemma is resolved, 9- to 12-year-old Latino, Asian, Black, and White children ( N = 108) completed a photo identification task in which acknowledging racial difference is beneficial to performance. Results indicate minority children are just as likely to avoid race as White children, and such avoidance exacted a cost to performance and nonverbal comfort. Results suggest that teachers are particularly important social referents for instilling norms regarding race. Norms that equate color blindness with socially appropriate behavior appear more broadly influential than previously thought, stifling talk of race even among those for whom it may be most meaningful.